Effect of miR-17 on Polygonum Cillinerve polysaccharide against transmissible gastroenteritis virus - Duan, Xueqin; Xu, Mengxin; Wang, Yunying; Liu, Nishang; Wang, Xingchen; Liu, Yingqiu; Zhang, Weimin; Ma, Wuren; Ma, Lin; Fan, Yunpeng (Frontiers in Veterinary Science, 2024)
The study aimed to investigate the impact of miR-17 on the polysaccharide of Polygonum Cillinerve (PCP) in combating transmissible gastroenteritis virus (TGEV). miR-17 was screened and transfection validation was performed by Real-time PCR. The function of miR-17 on PK15 cells infected with TGEV and treated with PCP was investigated by DCFH-DA loading probe, JC-1 staining and Hoechst fluorescence staining. Furthermore, the effect of miR-17 on PCP inhibiting TGEV replication and apoptosis signaling pathways during PCP against TGEV infection was measured through Real-time PCR and Western blot. The results indicated that miR-17 mimic and inhibitor could be transferred into PK15 cells and the expression of miR-17 significantly increased and decreased respectively compared with miR-17 mimic and inhibitor (P < 0.05). 250 μg/mL of PCP could inhibit cells apoptosis after transfection with miR-17. PCP (250 and 125 μg/mL) significantly inhibited the decrease in mitochondrial membrane potential induced by TGEV after transfection with miR-17 (P < 0.05). After transfection of miR-17 mimic, PCP at concentrations of 250 and 125 μg/mL significantly promoted the expression of mRNA of P53, cyt C and caspase 9 (P < 0.05). Compared with the control group, the replication of TGEV gRNA and gene N was significantly inhibited by PCP at concentrations of 250 and 125 μg/mL after transfection of both miR-17 mimic and inhibitor (P < 0.05). PCP at 62.5 μg/mL significantly inhibited the replication of gene S following transfection with miR-17 inhibitor (P < 0.05). These results suggested that PCP could inhibit the replication of TGEV and apoptosis induced by TGEV by regulating miR-17.